2009
DOI: 10.1016/j.nbd.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Alzheimer's disease

Abstract: Although a battery of neuropsychological tests are often used in making a clinical diagnosis of Alzheimer's disease (AD), definitive diagnosis still relies on pathological evaluation at autopsy. The identification of AD biomarkers may allow for a less invasive and more accurate diagnosis as well as serve as a predictor of future disease progression and treatment response. Importantly, biomarkers may also allow for the identification of individuals who are already developing the underlying pathology of AD such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 284 publications
(457 reference statements)
4
141
0
2
Order By: Relevance
“…The ratio of tau-epitopes to Aˇ42, in agreement with the precedent results, have also been found to be predictors of AD in MCI patients [67]. Other chemical components like CSF Isoprostanes which have been found to be increased in AD patients even in the preclinical stage [68] and ˛1-antichymotrypsin, Interleukin-6 and various markers of inflammation which have given ambiguous results [60], even if much less frequently, are also present in the literature. Recently, it has been concluded that the amount of CSF in the hippocampal region is also related to AD [69].…”
Section: Csfsupporting
confidence: 78%
See 2 more Smart Citations
“…The ratio of tau-epitopes to Aˇ42, in agreement with the precedent results, have also been found to be predictors of AD in MCI patients [67]. Other chemical components like CSF Isoprostanes which have been found to be increased in AD patients even in the preclinical stage [68] and ˛1-antichymotrypsin, Interleukin-6 and various markers of inflammation which have given ambiguous results [60], even if much less frequently, are also present in the literature. Recently, it has been concluded that the amount of CSF in the hippocampal region is also related to AD [69].…”
Section: Csfsupporting
confidence: 78%
“…In the recent years, some researches have focused on identifying reliable and valid biomarkers of AD in biofluids [60]. One of these biofluids is the CSF, which is a clear fluid that surrounds the brain and spinal cord mainly for protection.…”
Section: Csfmentioning
confidence: 99%
See 1 more Smart Citation
“…Altas concentraciones de t-tau junto a bajas concentraciones de Aβ 42 pueden detectar la EA con alta sensibilidad y especificidad 46 . Lo mismo ocurre para altas proporciones en concentración de f-tau/Aβ 42 47 , teniendo más potencial como biomarcador de diagnóstico que de progresión 48 .…”
Section: Biomarcadoresunclassified
“…Although some well-characterized biomarkers (e.g., tau protein and amyloid-␤42 in cerebrospinal fluid) and sophisticated neuroimaging instruments [e.g., magnetic resonance imaging (MRI) and fluorodeoxyglucose-positron emission tomography (FDG-PET)] have been shown to reliably detect early AD pathology [17], there are still some significant limitations to these approaches, such as low to moderate sensitivity and specificity of preclinical measurements, high costs, invasiveness, need of radioactive tracers, and the absence of standardization and clear diagnostic cutoff values [17][18][19]. Several reports over the past decade described the potential diagnostic importance of electrophysiological markers of cognitive decline in patients with MCI and the preclinical stage of AD, as obtained by analysis of the electroencephalography-derived event-related potentials (ERPs) [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%